2018
DOI: 10.3390/e20030177
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Entropy and Dimension of Financial Correlation-Based Network

Abstract: Abstract:We analyze the dimension of a financial correlation-based network and apply our analysis to characterize the complexity of the network. First, we generalize the volume-based dimension and find that it is well defined by the correlation-based network. Second, we establish the relationship between the Rényi index and the volume-based dimension. Third, we analyze the meaning of the dimensions sequence, which characterizes the level of departure from the comparison benchmark based on the randomized time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…PMFG is a network drawn in a plane, such that there are no intersecting links [17,38]. If N is total number of stocks, then it contains 3(N − 2) links.…”
Section: Planar Maximally Filtered Graphmentioning
confidence: 99%
“…PMFG is a network drawn in a plane, such that there are no intersecting links [17,38]. If N is total number of stocks, then it contains 3(N − 2) links.…”
Section: Planar Maximally Filtered Graphmentioning
confidence: 99%
“…Using MST and a hierarchical tree, Yang et al [ 28 ] mentioned the core nodes that should be monitored to maintain the stability and a slight increase in the clustering degree during a financial crisis for China’s stock market. Recently, Nie and Song [ 29 ] exhibited the integration of entropy and the dimension of financial correlation-based networks among stock markets of three countries: China, the UK, and the US. It is worth noticing that there are a lot of local stock markets that need to be explored via complex network methods, as past research is targeted at a few stock markets of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it can be noticed that various network entropies are defined, to describe the degree of network heterogeneity with different metrics. Li et al [ 55 ] found Shannon, Renyi, and Tsallis stock network entropy, evolving similarly over time. Xu [ 54 ] also discovered that network entropies constructed with node degree, clustering coefficient, and the shortest path length evolved with the same trend.…”
Section: Resultsmentioning
confidence: 99%
“…Among the rare examples are Li et al [ 53 ] who considered three types of network entropies to analyze the financial market. Nie and Song [ 55 ] introduced a standardized Rényi entropy to capture the structural differences of financial correlation-based networks. Caraiani [ 56 ] employed singular-value decomposition entropy to study comovement among various financial networks.…”
Section: Net Entropy Of a Stock Marketmentioning
confidence: 99%